Analysis of the most relevant anthropometric dimensions for school furniture selection based on a study with students from one Chilean region - Castellucci, H. I. (2015)
Most of the worldwide standards used for furniture selection suggest the use of the Stature of the school children, assuming that all the other anthropometric characteristics will also be appropriate. However, it is important to consider that students' growth differ with age. The aim of this study is to determine if Popliteal Height can be used as a better, or more adequate, measure for classroom furniture selection when comparing with Stature. This study involved a representative group of 3046 students from the Valparaíso Region, in Chile. Regarding the methodology, eight anthropometric measures were gathered, as well as six furniture dimensions from the Chilean standard. After assigning the level of school furniture using Stature and Popliteal Height to each of the students, six mismatch equations were applied. The results show that when using Popliteal Height, higher levels of match were obtained for the two more important furniture dimensions. Additionally, it also presents a better cumulative fit than Stature. In conclusion, it seems that Popliteal Height can be the most accurate anthropometric measure for classroom furniture selection purposes.